Diseases of the mucous membrane and the activity of the galvanic cell in the oral cavity - N. A. Volkov; N. Zh. Dikopova; A. G. Volkov; G. E. Amanatidi; Z. M. Abaev; I. A. Nikolskaya (Эндодонтия Today, 2024)
AIM. The objective of this study is to determine the frequency of detection of active galvanic cells in the oral cavity in the absence and presence of diseases of the oral mucosa, the development of which may be associated with the irritating effect of direct electric current.MATERIALS AND METHODS. Two groups of 50 patients were examined. All patients had at least 2 metal structures in the oral cavity. The first group comprised patients who had no diseases of the mucous membrane, the second group comprised patients with diseases of the oral mucosa. To detect metal structures that could form a galvanic pair, the electrochemical potential of each metal structure was determined and the difference between the potentials obtained was calculated. To determine the activity of a galvanic element formed by galvanic vapors, the hydrogen index of the gingival fluid in the area of these structures was determined.RESULTS AND DISCUSSION. The difference in the electrochemical potentials of metal structures in the studied groups had no statistically significant differences (p > 0.05) and amounted to 129 + 24.7 mV in the first group, to 135 + 19.8 mV in the second. In the first group, 92 % of patients had no significant difference in the hydrogen parameters of gingival fluid near pairs of metal structures (p > 0.05). The hydrogen values were 6.6 + 0.26 at the cathode and 6.9 + 0.35 at the anode. In the second group, in 88 % of patients, when measuring the hydrogen index of the gingival fluid, a high difference in pH values from 0.7 to 1.5 units was found. The values of hydrogen parameters near the cathode were 7.8 + 0.29, and the will of the anode was 6.3 + 0.22 (p < 0.05).CONCLUSION. Measuring the hydrogen parameters of the gingival fluid near metal structures forming a galvanic pair makes it possible to assess the activity of a galvanic cell. In the absence of diseases of the oral mucosa, the detection rate of active galvanic cells was only 8 %, and in diseases of the mucous membrane, active galvanic cells were detected in 88 % of patients.